CONTEXTUALIZATION OF SULUK CANDRA’S CHARACTER VALUES - Maknun, Moch Lukluil; Muzayanah, Umi (Center for Research and Development of Religious Literature and Heritage, 2020)
Indonesia's education is heavily promoting education on characters. Exploring the values of character as legacy of the previous generations can be done through scriptures. Of any genres of Javanese scriptures very rich in character values is the wulang script. One of the wulang scripts found in Surakarta is Suluk Candra written by Prince Wijil Kadilangu and stored in Museum Rekso Pustaka Mangkunegaran Library . This article tries to explore the character values in it and to contextualize it with today?s education. The method used in this study is principle working of philology and interpretation of texts.. The working principle of philology aims to produce a text edition, while interpretation aims to analyze the content of the text. The results of this study are as follows. Suluk Candra is a script containing Islamic values. At least this Suluk teaches four ethics that can be contextualized with the world of education in the current 4.0 era. The ethical findings are ethics to the king/ leader/ state, ethics to teachers, ethics to fellow human beings, and ethics to oneself. In addition to values of ethics, values of character education are also found in Suluk Candra. Those character values are relevant to the present days, including love of science, logical thinking, critical, creative, innovative, religious, honest, and nationalist.